2005
DOI: 10.1101/gr.4041005
|View full text |Cite
|
Sign up to set email alerts
|

An atlas of human gene expression from massively parallel signature sequencing (MPSS)

Abstract: We have used massively parallel signature sequencing (MPSS) to sample the transcriptomes of 32 normal human tissues to an unprecedented depth, thus documenting the patterns of expression of almost 20,000 genes with high sensitivity and specificity. The data confirm the widely held belief that differences in gene expression between cell and tissue types are largely determined by transcripts derived from a limited number of tissue-specific genes, rather than by combinations of more promiscuously expressed genes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
151
1
4

Year Published

2007
2007
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(171 citation statements)
references
References 20 publications
15
151
1
4
Order By: Relevance
“…Many of the 15,000 mRNAs observed in each sample were represented by only a few reads, likely indicative of either low-abundance cell types in the sample or transcriptional ''leakage.'' A prior study using massively parallel signature sequencing (MPSS) of mRNAs in human tissues concluded that Ϸ50% of the genes in the human genome are expressed in a tissue (21). Consistent with this, we observed Ϸ10,000 genes at a threshold of 20 reads per gene (Table 1 and Fig.…”
Section: Resultssupporting
confidence: 74%
“…Many of the 15,000 mRNAs observed in each sample were represented by only a few reads, likely indicative of either low-abundance cell types in the sample or transcriptional ''leakage.'' A prior study using massively parallel signature sequencing (MPSS) of mRNAs in human tissues concluded that Ϸ50% of the genes in the human genome are expressed in a tissue (21). Consistent with this, we observed Ϸ10,000 genes at a threshold of 20 reads per gene (Table 1 and Fig.…”
Section: Resultssupporting
confidence: 74%
“…18 Results from the latest generations of genome-tiling microarrays and high-throughput sequencing indicate that there may be a considerably richer universe of non-coding RNAs of various sizes, produced from many different regions of the genome, than had been previously supposed. [19][20][21] In addition, comparisons between animals with increasingly complicated bodies have been used to suggest that the proportion of non-coding RNA to protein-coding RNA is correlated with developmental complexity. [22][23][24] MicroRNAs Mature microRNAs are single-stranded RNA molecules that are approximately 21 or 22 nucleotides long.…”
Section: Discovery Of Small Rnamentioning
confidence: 99%
“…In an attempt to resolve this and to identify new CT antigens, we have taken an in silico approach to produce a comprehensive survey of CT gene expression profiles by combining expression information from an existing corpus of Ͼ8,000 cDNA libraries (16) together with the depth and resolution provided by massively parallel signature sequencing (MPSS) expression libraries (17), cap-analysis of Gene Expression (CAGE) libraries (18), and a survey using semiquantitative reverse-transcription PCR (RT-PCR) on a panel of 22 normal tissues. As a result, we have created a coherent classification of CT genes, and new CT genes have been identified using well-informed, structured prediction and confirmation criteria.…”
mentioning
confidence: 99%